Immune function and the role of vaccination after splenic artery embolization for blunt splenic injury. Issue 1 (January 2022) - Slater, Samuel J; Lukies, Matthew; Kavnoudias, Helen; Zia, Adil; Lee, Robin; Bosco, Julian J; Joseph, Tim; Clements, Warren
Abstract: The spleen is the most commonly injured solid organ following blunt abdominal trauma. Over recent decades, splenic artery embolization (SAE) has become the mainstay treatment for haemodynamically stable patients with high-grade blunt splenic trauma, with splenectomy the mainstay of treatment for unstable patients. Splenic function is complex but the spleen has an important role in immune function, particularly in protection against encapsulated bacteria. Established evidence suggests that following splenectomy immune function is impaired resulting in increased susceptibility to overwhelming post-splenectomy infection, however, immune function may be preserved following SAE. This review will discuss the current state of the literature on immune function following different treatments of blunt splenic injury, and the controversies surrounding what constitutes a quantitative test of splenic immune function.